Intraocular Sensors: Biocompatible Multifunctional Black‐Silicon for Implantable Intraocular Sensor (Adv. Healthcare Mater. 4/2017). Issue 4 (February 2017) - Lee, Jeong Oen; Narasimhan, Vinayak; Du, Juan; Ndjamen, Blaise; Sretavan, David; Choo, Hyuck
Abstract : In article number 1601356, Hyuck Choo and co‐workers report the first demonstrated use of high‐aspect‐ratio black‐silicon (b‐Si) as a multifunctional layer on an optically probed implantable intraocular pressure (IOP) sensor, a crucial device for glaucoma management and drug delivery. The anti‐reflective and anti‐biofouling properties of b‐Si significantly improved sensor readout performance and long‐term reliability in in vivo studies, bring this IOP‐sensing approach a step closer to practical use in medicine.